1994
DOI: 10.1007/bf00193485
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood concentrations of mefloquine enantiomers in healthy Thai volunteers

Abstract: We studied the pharmacokinetics of the enantiomers of mefloquine in whole blood in healthy Thai volunteers after administration of a single oral dose of 750 mg of the racemic mixture. Mefloquine pharmacokinetics were stereoselective. The peak concentrations and areas under the curve of the (-) enantiomer were significantly higher than those of its antipode (0.79 versus 0.46 microgram.ml-1 and 402 versus 94 micrograms.h.ml-1). The half-lives of (-)MQ were significantly longer than those of (+)MQ (531 versus 206… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
1
5
0
2
Order By: Relevance
“…Similar findings have been reported in Thai volunteers given a Mefloquine (MQ), a quinoline methanol chemically related to quinine, is an important drug for malaria prophylaxis and single dose of 750 mg MQ [7]. The aims of the present study were to investigate the treatment of multi-drug resistant P. falciparum malaria.…”
supporting
confidence: 67%
“…Similar findings have been reported in Thai volunteers given a Mefloquine (MQ), a quinoline methanol chemically related to quinine, is an important drug for malaria prophylaxis and single dose of 750 mg MQ [7]. The aims of the present study were to investigate the treatment of multi-drug resistant P. falciparum malaria.…”
supporting
confidence: 67%
“…The higher AUC value in whole blood for (À)mefloquine was also observed in plasma samples after oral administration in adult Caucasian healthy subjects , adult Thai healthy subjects (Martin et al, 1994) and Thai malaria children (Bourahla et al, 1996). In contrast, after repeated oral administration of the racemic mixture in rats, plasma concentrations of ( þ )mefloquine were higher than those of its antipode (Baudry et al, 1997), opposite to those obtained after oral administration in humans and intraperitoneal injection in mice.…”
Section: Stereoselectivity In Blood Pharmacokineticsmentioning
confidence: 90%
“…Our data showed that, in BALB/c mice, the t 1/2 for the threo compounds was half that of the erythro compounds, which could explain, at least in part, our findings. It should be noted, however, that pharmacokinetic studies in healthy humans have shown that the halflife of (Ϫ)-erythro-mefloquine is significantly longer than that of (ϩ)-erythro-mefloquine; no stereoselectivity was seen for values of time to maximum concentration of drug in serum (T max ) (18). Similar results were observed in adults with uncomplicated multidrugresistant falciparum malaria, where the mean ratio between the concentrations of the (Ϫ)-and (ϩ)-enantiomers of erythro-mefloquine was 3.37 (12).…”
Section: What Could Explain the Different Activities Among The Enantimentioning
confidence: 99%